2016
DOI: 10.1021/acscatal.5b02720
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Enhanced Reactivity of μ-Nitrido-Bridged Diiron(IV)-Oxo Porphyrinoid Complexes over Cytochrome P450 Compound I

Abstract: μ-Nitrido-bridged diiron porphyrins and phthalocyanines are known to be efficient oxidants that are able to oxidize some of the strongest C−H bonds in nature, such as the one in methane. The origin of their catalytic efficiency is poorly understood, and in order to gain insight into the structural and electronic features of this chemical system, we performed a detailed and systematic study into their chemical properties and reactivities using density functional theory. Our work shows that μ-nitrido-bridged dii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 104 publications
7
92
1
Order By: Relevance
“…49 The correlations of these parameters with the Hammett parameter σ P are shown in Figure 6. Thus, we calculated the one-electron ionization energy of all substrates ( IE SubZ ) and the one-electron reduction of [Mn(O)(H 8 Cz)(CN)] − ( EA MnO ).…”
Section: Resultsmentioning
confidence: 99%
“…49 The correlations of these parameters with the Hammett parameter σ P are shown in Figure 6. Thus, we calculated the one-electron ionization energy of all substrates ( IE SubZ ) and the one-electron reduction of [Mn(O)(H 8 Cz)(CN)] − ( EA MnO ).…”
Section: Resultsmentioning
confidence: 99%
“…[6] To gain insight into the structure and reactivity of enzymatic intermediatesa nd understandt he effect of ligand features and their direct environment, al arge number of biomimetic modelsh ave been generated and investigated. [7] These studies have given insighti nto the effect of the ligand coordination, [8] spin-state ordering, [9] and hydrogen-bonding interactions [10] that affect the properties and reactivity of the oxidants. In particular, it was found that nonheme iron(IV) oxo is more reactive in the quintets pin state than in the triplet spin state, probably due to exchange stabilization of the products tructures.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, UB3LYP/LACV3P(Fe), 6‐311+G*(all atoms) calculated barriers for methane hydroxylation with 3, 3‐Ac and CpdI are in an ascending order: 15.7, 19.4 and 25.9 kcal/mol respectively. Interestingly, the calculated strength of the OH bond formed after hydrogenation of the metal‐oxo center in 3 , i. e. BDE OH ( 3 ) is highest at 86.7 kcal/mol followed by BDE OH ( 3‐Ac ) at 82.3 kcal/mol, and BDE OH ( CpdI ) at 79.6 kcal/mol . Hence, it can be inferred that a greater bond dissociation energy of the metal‐OH moiety ensures a lower energetic penalty for its formation, thus lowering the barrier for HAT process.…”
Section: Thermochemical Controlmentioning
confidence: 99%
“…Notably, the bond dissociation energy of methane C−H bond is 104.9 kcal/mol. As evident from the thermochemical cycle, BDE OH can be split up into two major constituents: electron affinity of the oxidant (interpreted from E °) and proton affinity of the reduced oxidant (obtained from p K a ) . Hence, dissecting the bond dissociation energies revealed that electron‐push effect from the axial ligand to the oxo group has marked impact on the relative acidity of the metal‐hydroxo bond.…”
Section: Thermochemical Controlmentioning
confidence: 99%